Extraction of fat/oil from fleshing by-product using a wet rendering process and combination with organic solvents - Sugihartono Sugihartono; Dona Rahmawati; Ageng Priatni; Efa Radnawati (Majalah Kulit, Karet, dan Plastik, 2019)
The extraction of fat/oil from fleshing by-products using moist heating (boiled and steamed) produces a fat that contains large amounts of impurities and which is bluish color, whereas when using fatty solvents, it is necessary to dry the ingredients. The purpose of this study was to determine the fat/oil characteristics from fleshing by-products extracted using a combination of wet rendering (temperatures of 80, 90 and 100 °C, and times 1, 2 and 3 hours) with n-hexane. The combined treatment of wet rendering (temperature 90 °C and duration 2 hours) with n-hexane gave rise to the production of fat with the highest yield (11.10% w/w). The higher the temperature and the longer the wet rendering process, results in fat with higher levels of free fatty acid and the saponification value, but the lower the number of peroxides and the darker the color. The fats/oils consist of 37 fatty acid compounds, composed of saturated and unsaturated fatty acids. There are six very present fatty acid compounds, namely butyric acid methyl ester, tetradecanoic acid methyl ester, cis-10-pentadecanoic acid methyl ester, palmitoleic acid methyl ester, octadecanoic acid methyl ester and trans-9-elaidic acid methyl ester.